Amblyopia with Eccentric Fixation: Is Inverse Occlusion Still an Option?. Issue 4 (2nd October 2019) - Godts, Daisy Jozef Margaretha; Mathysen, Danny Godelieve Peter
ABSTRACT: Purpose : To present a treatment protocol for patients with amblyopia and eccentric fixation who do not respond to conventional occlusion therapy. Material and methods : In this consecutive case series, 11 patients were included (age 3.5 to 5.0), all with mixed amblyopia and eccentric fixation, who had only minor improvement of their visual acuity (VA) despite good compliance with 6 hours/day to full time occlusion of the sound eye for at least 6 months. Visual acuity of amblyopic eyes ranged from 20/50 to 20/400 at the time of initiation of inverse occlusion. Total inverse occlusion of the amblyopic eye was prescribed for 4 to 8 weeks to convert the steady eccentric fixation to wandering fixation. No binocular viewing was allowed. Once the fixation became wandering, the sound eye was occluded day and night and in most patients, a red filter was placed before the amblyopic eye to stimulate foveal fixation. In nine patients, the fixation became central and occlusion of the sound eye was continued without red filter. All children continued full time occlusion until VA failed to improve after two consecutive visits despite good compliance. Results : In nine children, the VA improved to at least 20/32 in the amblyopic eye. The VA of the sound eye did not change. Conclusion : Inverse occlusion is still a valuable option if conventional occlusion appears to be insufficient to improve VA in amblyopic eyes with eccentric fixation. Full time inverse occlusion should be performed until the eccentric point is no longer used for fixation and should be followed with full time occlusion of the sound eye. Placing a red filter before the amblyopic eye may be helpful to stimulate foveal fixation.